Continuance adoption of mobile-based payments in Covid-19 context: an integrated framework of health belief model and expectation confirmation model. Issue 4 (24th July 2020) - C.C., Sreelakshmi; Prathap, Sangeetha K.
Abstract : Purpose: Shifting to mobile-based banking transactions from physical banking transactions can be considered as a social distancing mechanism, which helps to prevent the spread of Covid-19 virus. As the spread of Covid-19 is expected to continue for long, the continued usage of mobile-based payment services as a strategy to maintain social distancing has to prevail. Hence, this study aims to propose an integrated framework of mobile payments adoption and its continuance intention by integrating health belief model (HBM) and expectation confirmation model (ECM) of information system continuance. Design/methodology/approach: The subject of the study constitutes new adopters of mobile payments. A total of 654 respondents participated in the survey. The conceptual model was empirically validated using structural equation modeling and serial mediation analysis. Findings: The study found that the HBM constructs, namely, perceived severity, perceived susceptibility and self-efficacy significantly influenced adoption/confirmation of mobile-based payment services. The continuance intention was significantly predicted by perceived usefulness and perceived satisfaction. Furthermore, the perceived health threat (comprising perceived severity and perceived susceptibility) indirectly affects continuance intention through confirmation, perceived usefulness and satisfaction. Practical implications: There are short-term and long-term implications for the study. Short-term implications include triggering the HBM at policy levels, to adopt mobile payments/banking as a means of social distancing in the wake of the increasing threat of Covid-19 in India. Long-term implication for service providers is to convert adopters into loyal consumers by enhancing usefulness and satisfaction. Originality/value: The study proposes a novel attempt to explain the adoption and continuance of mobile-based payment as a preventive health behavior to contain the spread of Covid-19 outbreak. The study proposes an integrated framework of HBM and ECM to explain pre-adoption and post-adoption behavior of consumers with respect to mobile-based payment services during Covid-19 context.